Contributive Culture of Microlearning through Telegram (Docentes 2.0 Journal, 2022)
Any act in the will brings with it development and civilization, while tax events generate discomfort for citizens, consequently leaving personal stagnation and limited national growth. The omission or falsity of the tax obligations come from extensive tax information, confusing and poorly disclosed, by the tax authorities, leaving a valuable opportunity to carry out this study. The objective of the present investigation was to generate an understanding of the tax culture the students of the Polytechnic University of the Valley of Mexico, in the career in Administration and business management, on rights and obligations attributable to taxpayers, through a technological resource called "NPC Learn culture-contributory" taught through Telegram. This proposal is based on the action-research method, socio-critical paradigm, qualitative approach, collaborative design, critical-emancipatory-practical type, and cross-section, focused on learning and awareness of the actors. The universe was made up of students from the Polytechnic University of the Valley of Mexico, while its sample concerns twenty-four subjects, studying the subject of Tax Contributions. Surveys via Google Drive and face-to-face discussion forums were used to collect information. Therefore, according to the experience obtained, it is essential to point out how the citizen understands the fiscal structure in Mexico.
Keywords: Telegram channel; microlearning; contributory culture